WIELOJĘZYCZNOŚĆ I MIĘDZYKULTUROWOŚĆ W POLSKIM KONTEKŚCIE EDUKACYJNYM – REALISTYCZNE CELE CZY MITY EDUKACYJNE? - Pawlak, Mirosław (Neofilolog, 2018)
Over the last decade or so, mainly under the influence of the Common European Framework of Reference for Languages, it has been assumed, often entirely uncritically, that the key goals of foreign language peda-gogy should be the development of multilingualism and multicultural-ism. Although these goals are barely mentioned in the current core cur-riculum and they do not really find a reflection in coursebooks or every-day teaching practice, the pedagogical recommendations stemming from numerous conference presentations, research studies or methodology textbooks for pre-service and in-service teachers indicate that such a sit-uation should be subject to change because it is not sufficiently reflective of the latest theoretical proposals. A question arises, however, to what extent these goals can in fact be accomplished in our educational context in which additional languages are taught and learned as foreign rather than second, and, despite increasing opportunities in this respect, out-of-school contact with such languages is often still very limited. The pa-per aims to address this question, mainly focusing on the difficulties in-volved in fostering multilingualism and multiculturalism, both with re-spect to the relevant regulations concerning language education in Po-land, everyday realities of foreign language teaching and learning, the limitations of teacher training as well as problems involved in conducting empirical studies.